Comparable efficacy of platelet-rich plasma against platelet-poor plasma in stable vitiligo on concurrent psoralen+sunlight therapy: a hospital-based open-labeled study - Neni Agarwal; Pratik Gahalaut; Nitin Mishra; Madhur Kant Rastogi; Mriganka Mehra; Ajitesh P Varshney (Wolters Kluwer Medknow Publications, 2021)
Background There is a constant search for an ideal treatment for vitiligo. Platelet-rich plasma (PRP) is a novel modality for treating stable vitiligo. Presently, literature regarding the efficacy of combining either PRP or platelet-poor plasma (PPP) with psoralen+sunlight (PUVASOL) in vitiligo does not exist. Objective This study compares the safety and efficacy of combining PUVASOL with either PRP or PPP against PUVASOL alone in patients with stable nonsegmental vitiligo. Patients and methods This prospective, open-labeled, comparative study was done in 20 patients with stable nonsegmental vitiligo, each having at least three vitiligo patches of similar shape and size. All the patients received PUVASOL as standard treatment modality. PRP or PPP was injected into two separate study patches as an adjuvant treatment with PUVASOL; however, the third patch acted as a control and was treated by PUVASOL alone. These patients were followed up for 4 weeks after the end of four treatment sessions. Results Compared with control areas (exposed to PUVASOL only), statistically significant more repigmentation was seen in areas treated with a platelet preparation (either PRP or PPP) along with PUVASOL. However, there was no significant difference between PRP and PPP arm (P=0.824) as per qualitative and quantitative assessment. Conclusion Addition of a platelet preparation (either PRP or PPP) had an additive beneficial effect on the response of PUVASOL therapy in patients with stable vitiligo at the study end point of 16 weeks. However, PRP and PPP showed comparable efficacy at the study end point in terms of repigmentation when used in conjunction with PUVASOL.